Parental stress, mental health, and child traits in Italian mothers and fathers of autistic children - Perzolli, Silvia; Bertamini, Giulio; Venuti, Paola; Bentenuto, Arianna (Frontiers in Psychology, 2025)
IntroductionSeveral studies have investigated differences between mothers' and fathers' stress and mental health in the context of autistic children parenting. However, fewer have examined differences in parent-reported perceptions of their children's behaviors, symptom severity, and their associations with parental variables. This study aimed to compare parental stress (Parental Stress Index—Short From), mental health (Symptom Checklist–90), and parent-reported perceptions of child behaviors (Child Behavior Checklist—CBCL) and symptom severity (Social Responsiveness Scale—SRS). In Italian mothers and fathers of autistic children while exploring how parental wellbeing relates to both parent-reported and clinically assessed child characteristics.MethodsA total of 102 parents (51 mothers and 51 fathers) of autistic children aged 4–19 years completed questionnaires assessing stress, mental health, children's behavioral traits and symptom severity. Standardized clinical tests directly measured children's cognitive functioning (IQ) and symptom severity. Group differences between mothers and fathers were analyzed using inferential tests, while Linear Mixed Models were employed to examine the effect of parent, parental stress and mental health on parent-reported perceptions of children's behaviors and symptom severity, as well as clinically measured children's cognitive functioning and symptoms severity.ResultsMothers and fathers reported similar stress levels but mothers showed higher levels of mental health symptoms and perceived their children as having more severe internalizing and externalizing behaviors and more severe symptomatology compared to fathers. Parental mental health was significantly associated with parent-reported child internalizing behaviors, while parental stress was linked to externalizing behaviors and parent-reported autism severity. No effects emerged for child cognitive functioning, and the model on clinician-rated autism severity failed to converge.DiscussionThese findings emphasize the interconnected nature of parental wellbeing, parent-reported child characteristics, and clinically assessed child traits. Recognizing these links may inform more effective, targeted support strategies for families raising autistic children.